2015
DOI: 10.1161/circresaha.115.306886
|View full text |Cite
|
Sign up to set email alerts
|

Wnt10b Gain-of-Function Improves Cardiac Repair by Arteriole Formation and Attenuation of Fibrosis

Abstract: Rationale Myocardial infarction causes irreversible tissue damage, leading to heart failure (HF). We recently discovered that canonical Wnt signaling and the Wnt10b ligand are strongly induced in mouse hearts after infarction. Wnt10b regulates cell fate in various organs, but its role in the heart is unknown. Objective To investigate the effect of Wnt10b gain-of-function on cardiac repair mechanisms and assess its potential to improve ventricular function after injury. Methods and Results Histological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 60 publications
1
51
0
Order By: Relevance
“…Moreover, in the context of complicated [5,9,13,16,32] and multifaceted roles of the WNT pathway in infarct repair in the existing literature, our data may speak to the potential of temporally regulated scalable pharmacologic WNT inhibition in reconciling the discordant observations based on genetic models [6,7,14] of WNT modulation. With additional details on the mechanism-of-action and safety data emerging with continuing studies, and ongoing clinical trials [23], GNF-6231 and the new class of Porcupine inhibitors hold significant potential as effective therapeutics for cardiac regeneration.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Moreover, in the context of complicated [5,9,13,16,32] and multifaceted roles of the WNT pathway in infarct repair in the existing literature, our data may speak to the potential of temporally regulated scalable pharmacologic WNT inhibition in reconciling the discordant observations based on genetic models [6,7,14] of WNT modulation. With additional details on the mechanism-of-action and safety data emerging with continuing studies, and ongoing clinical trials [23], GNF-6231 and the new class of Porcupine inhibitors hold significant potential as effective therapeutics for cardiac regeneration.…”
Section: Discussionmentioning
confidence: 62%
“…In this study, we focused exclusively on the effects of Porcupine inhibition through the β-catenin-dependent arm of the WNT pathway based on the significant body of literature suggesting a critical and complicated role—both maladaptive [6,7,30], and in some cases pro-reparative [13,14,16]—for this signaling cascade in infarct pathology. However, since GNF-6231 targets Porcupine, its effects independent of canonical WNT pathway may also be important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using typical inflammatory gene markers, such as Il-1β and E-selectin , and markers of granulation tissue formation and fibrosis, such as Tgfβ1 and alpha Smooth Muscle Actin (α Sma ), we determined that pro-inflammatory genes are induced early and peak at days 1–2 after MI, whereas fibrosis genes are induced at day 5, as expected. 4,6,8 Gene induction of inflammatory genes returned to baseline levels between days 3 to 5, whereas Tgfβ1 expression returned to baseline at day 21. α Sma levels declined, but were still detectable at day 21, reflecting the presence of myofibroblasts during the scar maturation phase (Figure 1A). …”
Section: Resultsmentioning
confidence: 91%
“…6 We have recently demonstrated that canonical Wnt signaling activation after MI attenuates fibrosis and promotes arteriole formation and cardiogenesis, suggesting that developmental pathways, critical for embryonic cardiac development, are re-activated after injury in the adult heart to regulate tissue repair. 7,8 …”
Section: Introductionmentioning
confidence: 99%